Combustion behaviour of plastic waste – A case study of PP, HDPE, PET, and mixed PES-EL. (20th May 2023) - Mentes, Dóra; Nagy, Gábor; Szabó, Tamás J.; Hornyák-Mester, Enikő; Fiser, Béla; Viskolcz, Béla; Póliska, Csaba
Abstract: Plastic production is skyrocketing due to convenience needs and thus, the amount of plastic waste is increasing. There are several different methods to handle plastic waste, within which waste-to-energy processes are viable options in certain settings. However, the combustion of materials is a complicated and complex process that can take place in a number of ways. When exposed to heat, different polymers behave differently ( e.g. have different emission factors) and thus, not all types of plastic waste recommended to be handled through combustion. Therefore, it is vital to achieve a deeper understanding of these processes in order to decide on the end use of plastic materials. Four common types of polymers were studied: polypropylene (PP), high-density polyethylene (HDPE), polyethylene terephthalate (PET), and polyester-elastane (PES-EL) mixture. The combustion properties of the plastic materials were investigated. The experiments were carried out in a laboratory electric resistance tube furnace at two different temperatures (650 and 900 °C). The behavior of these mainly single-use plastic wastes and the changes in the concentrations of CO, CO2, NOx, and O2 flue gas components generated during combustion was studied to determine the quality of potential waste-to-energy processes. Highlights: Combustion of aliphatic (PP, HDPE) and aromatic (PET, PES) plastics studied. Aliphatic waste decomposes with intense fragmentation. Aromatic compounds (PET, PES) burn without flame at 650 °C. Increasing the temperature, the combustion quality of aromatic compounds increased. PP and HDPE are recommended for thermal combustion (heat generation).